LEGAL ISSUES CONNECTED WITH BUILDING INFORMATION MODELING (BIM) - ALHADDAD, AHMED EID (2016)
The primary objective of this dissertation study was to explore and explain various legal concerns and issues related to building information modeling (hereinafter referred to as “BIM”). The secondary objective of this research was to highlight the advantages of BIM implementation in different fields. In a nutshell, the present study was carried out in the form of a mixed research design. The next advantage of this study stems from the fact that the conducted research not only underlined the advantages of BIM implementation, but also underscored major problems and challenges that need to be addressed in the course of implementation. As a result of the study, it was established that BIM is not merely one of several available models of interaction, but that is an up-to-date and advanced model that set forth for consideration a new philosophical paradigm for practice, particularly due to its intrinsic capacity of encouraging both the combination and practical actualization of different roles of all participants in a concrete project. On the other hand, a noticeable benefit of this study is that the research findings and inference clearly illustrate how Building Information Modeling (BIM) can make significant contributions to the development of construction industry. The aforesaid illustration became possible, particularly when it was established by means of research that the salient features of BIM implementation have direct relationships with a multiplicity of office products, such as word processing, graphic products, and spreadsheets. The findings of this study contain applied knowledge and guidance on how to utilize BIM in ship-building, aviation, automobile, and other industries.